Роль транснаціональних корпорацій у формуванні інвестиційної безпеки України - Соколовська, О. М.; Соколовская, Е. Н.; Sokolovska, O. (ЦНТУ, 2019)
У статті проаналізовано діяльність найбільших транснаціональних корпорацій в Україні. Розглянуто основні тенденцій зміни обсягів та структури прямих іноземних інвестицій в Україні. Визначено невідповідність граничному значенню показника відношення прямих іноземних інвестицій до ВВП як одного з основних індикаторів інвестиційної безпеки, що пов’язаний з діяльністю транснаціональних корпорацій. Виявлено позитивну тенденцію зростання частки інвестицій у високотехнологічні галузі промисловості в загальних обсягах прямих іноземних інвестицій, а також у такі сфери послуг, як оптова та роздрібна торгівля, інформація та телекомунікація, що свідчить про позитивний вплив транснаціональних корпорацій на економічний розвиток в Україні. В статье проанализирована деятельность крупнейших транснациональных корпораций в Украине. Рассмотрены основные тенденции в изменении объемов и структуры прямых иностранных инвестиций в Украине. Определено несоответствие граничного значения показателя отношения прямых иностранных инвестиций к ВНП как одного из основных индикаторов инвестиционной безопасности, который связан с деятельностью транснациональных корпораций. Выявлена позитивная тенденция роста доли инвестиций в высокотехнологической отрасли промышленности в общих объемах прямых иностранных инвестиций, а также в такой сфере услуг, как оптовая и розничная торговля, информация и телекоммуникация, что свидетельствует о положительном влиянии транснациональных корпораций на экономическое развитие Украины. The article highlights that the issue of transnationalisation has recently become one of the basic tendencies in the process of the world economic development. Apart from the advantages arising as a result of investment intensification and growth of commercial and technological exchange, there appears a great deal of economic threats manifested in the increase of international imbalance, competitive market framework defamation and the interference of international corporations in the recipient country's interests. The analysis of the transnational corporations performance in Ukraine shows that they deal mostly with the fields of food, drinks and tobacco production, banking, wholesale and retailing. It can be proved by the amount of taxes paid the state budget and the direct foreign investment share in the mentioned industries. In Ukraine the level of general investment security has recently decreased. Meanwhile, in the long-term period there has been a deterioration in the overall ratio of the direct foreign investment to gross domestic product which doesn't meet the requirements of the economic security. Some positive tendency in the field of investment security can be observed in the gradual growth of high-tech industries share as a part of general direct foreign investment, as well as in the wholesale, retailing, information technologies and telecommunication. Relative increase in the knowledge intensity of foreign investments is the indication of the positive role of transnational corporations in the process of the postindustrial economic restoration based on the knowledge. A certain decrease in the foreign investors' interests in the spheres of financial services and insurance, as well as the reduction of investments in the fields of healthcare, education and science, indicate the growth of investment risks as a result of banking and healthcare reforms and slow institutional transformations.
Роль транснациональных корпораций в формировании инвестиционной безопасности Украины
Role of Transnational Corporations in the Building of Investment Security of Ukraine
Keywords: транснаціональні корпорації; прямі іноземні інвестиції; інвестиційна безпека; транснациональные корпорации; прямые иностранные инвестиции; инвестиционная безопасность; transnational corporations; direct foreign investment; investment security